Diabetes Mellitus as One of the Risk Factors Contribute to Carcinogenesis - Noorwati Sutandyo (National Cancer Center - Dharmais Cancer Hospital, 2020)
Diabetes mellitus (DM) and cancer are both global diseases whose numbers continue to grow. Higher risk of developing cancer in diabetic patients, especially in liver, endometrial, pancreatic, kidney, colorectal, bladder, and breast cancer, was already shown in several previous studies. This review will explain the possible DM pathogenesis that plays a role in carcinogenesis using the simple but thorough concept of insulin resistance, hyperglycemia, and chronic inflammation. By knowing the link, it is hoped that this review can be useful in developing cancer prevention plans for those with diabetes.